Population viability in data deficient nomadic species: What it will take to save regent honeyeaters from extinction. (February 2022) - Heinsohn, Robert; Lacy, Robert; Elphinstone, Andrew; Ingwersen, Dean; Pitcher, Benjamin J.; Roderick, Mick; Schmelitschek, Emily; Van Sluys, Monique; Stojanovic, Dejan; Tripovich, Joy; Crates, Ross
Abstract: The long-distance, unpredictable movement patterns of nomadic species make them challenging to monitor and conserve. Critically endangered regent honeyeaters Anthochaera phrygia once roamed south-eastern Australia in 'immense flocks' but now number fewer than 300 wild birds over a vast 300, 000 km 2 range. Regent honeyeaters are a rare example where extensive monitoring data are now available for a nomadic species, enabling evaluation of the impact of management actions using population viability analysis (PVA). We combined demographic estimates from wild population monitoring in the 1990s, a zoo-based supplementation program and a contemporary range-wide monitoring program to simulate the wild population trajectory under various management and climatic scenarios. Without intervention, our models predicted extinction within 20 years, and showed that management strategies at their current intensity have limited efficacy to prevent extinction. Conservation actions should aim to increase the size and density of the wild population so that Allee effects no longer suppress population growth. Protection of wild regent honeyeater nests is essential as breeding success has declined over recent decades and droughts increasingly reduce breeding opportunities. Our models emphasise the need for zoo-based breeding to bolster the wild population, but show that release of zoo bred birds into the wild only slows the rate of population decline. To recover the wild regent honeyeater population, the next five years will be critical for implementing the most effective conservation strategy. This requires a combination of nest protection and release of zoo-bred birds with improved fitness, predator suppression, habitat protection and increased rates of habitat restoration.